Changes in quality of goat meat after alterations in animal Handling - doi:10.5020/18061230.2007.p33 - Frederico José Beserra; Eurídice Ribeiro de Alencastro; José Maria dos Santos Filho; Selene Maia de Morais; Roselúcia Barrozo de Almeida (Universidade de Fortaleza, 2012)
This study aimed at evaluating the effect of animal handling, consisting in castration and cashew nut diet supplementation, on the cholesterol content and percentage composition of the muscles that constitute the leg meat cut from crossbred goats, grown in Ceará State. A case experimental design was applied with twenty male-animals with 5-6 months age and mean weight of 12 Kg, randomly divided in two groups of castrated (10) and intact (10) animals. In individual bays, they received during 5 months, two food regimen based on dried elephant grass (Pennisetum purpureum) and a standard isoproteic ration (corn and soy oil), one of them with the addition of 13% cashew nut bran (CNB), forming four sub-groups: A1 (intact with no CNB supplemented diet); A2 (intact with CNB supplemented diet); B1 (castrated with no CNB supplemented diet) and B2 (castrated with CNB supplemented diet). The castration associated with the CNB supplementation increased the meat's fat yield from 1.16% to 3.57% and the cholesterol content from 36.47 mg/100g to 62.30 mg/100g. The ash yield decreased from 1.14% to 1.04%. The castration isolated only reduced moisture yield from 75.98% on sub-group A2 to 74.19% on sub-group B2. In intact animals that fed diet supplemented with CNB the protein decreased from 20.58% to 18.85% (P < 0.05) (sub-groups A1 and A2). The increased cholesterol content was highly correlated with the increase of the fat (93%) In conclusion, these results showed that the combined use of castration and cashew nut bran (13%) diet negatively influenced the dietetic and nutritional quality of goat leg meat.